Gingival prosthesis: A treatment modality for recession - Pallavi Samatha Yalamanchili (Journal of Orofacial Sciences, 2013)
Gingival recession caused due to periodontal disease disturbs patients because of sensitivity and esthetics. Gingival prosthesis may be fixed or removable and can be made from silicones, acrylics, composite resins or ceramics according to what is best suited for the case. The gingival veneer is esthetically appealing and easy to maintain. This case report describes the use of gingival veneer as a treatment modality for recession.